MAIN FACILITY UTILIZATION OF CAROCOK TARUSAN COASTAL FISHING PORT WEST SUMATERA PROVINCE - Muthia Ayu Nuriza; T. Ersti Yulika Sari; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was conducted in June 2018 at Carocok Tarusan Coastal Fishing Port West Sumatera Province. The purpose of this study ti know the level of utilization of main facilities (docks, port pools, plaster, roads and land) at Carocok Tarusan Coastal Fishing Port. The method used is the survey method. Form the result of the study it was found the level of utilization on land is 54,33% with a total land  area of 2,19 ha, at the docks the level of utilization is 46,50% with a dock length of 100 m, at the port pools area the level of utilization is 61,00% with a port pool area of 30.000 m, at the depth of the port pools the level of utilization is 36,37% with the depth of the port pool of 8 m, at the plaster the level of utilization is 62,5% with a length of plaster 400 m.      Keywords :Level of Facility Utilization, Main Facility,  Carocok Tarusan Coastal Fishing Port.